Catalytic CO2-MEA absorptions with the aid of CaCO3, MgCO3, and BaCO3 in the batch and semi-batch processes. Issue 4 (2nd April 2020) - Shi, Huancong; Huang, Min; Huang, Yuandong; Cui, Mingqi; Idem, Raphael
Abstract: Three solid chemicals, CaCO3, MgCO3, and BaCO3, were tested to accelerate the CO2 absorption with monoethanolamine (MEA) solvents to verify the effect of heterogeneous catalysis. The experiments were conducted in a batch process at 20 ± 0.2 °C and a semi-batch process under room temperature. For the batch process tests, CaCO3, MgCO3, and BaCO3, accelerated the CO2 absorption with MEA solutions at 1, 3, and 5 mol/L, respectively. The overall absorption periods were reduced by around 39.5%, 36.8%, and 36.8% in 3 M solution; and 31.9%, 19.1%, and 26.6% in 5 M solution. For the semi-batch process tests, CaCO3 and MgCO3 accelerated the CO2 absorption with 5 M MEA solutions by 20% and 20%, from 57 s to 45 s to reach equilibrium at loading of 0.0 mol/mol, and 16% and 12% from 75 s to 63–66 s to reach equilibrium at loading of 0.20 mol/mol. These solid chemicals were good candidates of heterogeneous catalysts of CO2 –MEA absorption in an amine scrubbing process.